PUNCTATE INNER CHOROIDOPATHY–LIKE REACTIONS IN UNRELATED RETINAL DISEASES. Issue 11 (November 2022) - Cicinelli, Maria Vittoria; Marchese, Alessandro; Ramtohul, Prithvi; Miserocchi, Elisabetta; Introini, Ugo; Bandello, Francesco; Freund, K. Bailey; Battaglia Parodi, Maurizio
Abstract : Supplemental Digital Content is Available in the Text. A punctate inner choroidopathy–like reaction may occur in patients with apparently unrelated chorioretinal diseases. Our study expands the spectrum of reactive, inflammatory lesions presumably promoted by loss of the outer retinal immune privilege in pre-existent chorioretinal disorders. Abstract : Purpose: To report a cohort of patients with a punctate inner choroidopathy (PIC)-like reaction in concurrent, unrelated, chorioretinal disorders. Methods: This was a retrospective observational study of patients seen at two referral centers with lesions consistent with PIC on multimodal imaging; patients with lesions resembling idiopathic multifocal choroiditis were also included. Active PIC-like lesions appeared as focal hyperreflective lesions splitting the retinal pigment epithelium/Bruch membrane (RPE/BrM) complex on optical coherence tomography. Chronic PIC-like lesions included subretinal fibrosis, multifocal punched-out chorioretinal atrophy, and curvilinear streaks. Patients' demographics, additional imaging features, and treatment responses were collected and summarized. Results: Twenty-two eyes of 16 patients with a PIC-like reaction were included (75% females; median age 40 years). Underlying diagnoses included hereditary retinal conditions (10 patients, 63%) and acquired etiologies, all characterized by the RPE/BrM or outer retinal disruption. Fifteen eyes (68%) had active PIC-like lesions; seven eyes (32%) had chronic PIC-like lesions. Active PIC-like lesions regressed with time and responded to systemic steroids. Subretinal fibrosis (3 eyes, 20%), macular atrophy (3 eyes, 20%), and concomitant subretinal fibrosis and macular atrophy (5 eyes, 33%) developed on follow-up. Recurrences occurred in five eyes (23%). Conclusion: RPE/BrM or outer retina disruption may trigger a PIC-like reaction in susceptible patients, presumably because of the loss of immune privilege. A PIC-like reaction may influence the clinical progression and the visual prognosis of the primary chorioretinal disease.